1993
DOI: 10.1152/ajpcell.1993.264.6.c1513
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular free Na+ in resting and activated A7r5 vascular smooth muscle cells

Abstract: Regulation of intracellular Na+ ([Na+]i) in cultured vascular smooth muscle cells (A7r5 line) was studied with Na(+)-sensitive fluorescent dye sodium-binding benzofuran isophthalate. Digital imaging microscopy was used to study single-cell fluorescence. Na+ was distributed uniformly in cytoplasm and nucleus; mean Na+ concentration in resting cells was 4.4 +/- 0.3 mM in cytoplasmic areas ([Na+]cyt) and 4.5 +/- 0.4 mM in nuclear areas ([Na+]n). Na+ pump inhibition and cell activation evoked uniform changes in [N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(70 citation statements)
references
References 21 publications
4
64
2
Order By: Relevance
“…Purinergic stimulation, like vasopressin, 27 increases global [Na ϩ ] i in RASMCs, which we have linked to opening of a Na ϩ -permeable channel. 12 We propose that TRPC6- containing channels mediate this Na ϩ entry.…”
Section: Mechanism Of Global [Na ؉ ] I Elevationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Purinergic stimulation, like vasopressin, 27 increases global [Na ϩ ] i in RASMCs, which we have linked to opening of a Na ϩ -permeable channel. 12 We propose that TRPC6- containing channels mediate this Na ϩ entry.…”
Section: Mechanism Of Global [Na ؉ ] I Elevationsmentioning
confidence: 83%
“…28 However, our laboratory and several others have shown that NCX-mediated Ca 2ϩ entry is essential to purinergically and adrenergically stimulated Ca 2ϩ influx in intact blood vessels and cultured aorta smooth muscle cells. 6 27 and were partly attributed to Na ϩ entry via NCX and store-operated channels. 27 We show here that agonist stimulation also causes localized [ …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osmolality was kept constant by the addition of choline chloride. The solution also contained ouabain (5 ϫ 10 Ϫ3 M) and the Na (16,19). The intracellular Na ϩ (Na ϩ i ) calibration curve was found to be almost linear from about 1 to 20 mM, the physiological intracellular range, and a change of less than 0.5 mM Na …”
Section: Methodsmentioning
confidence: 99%
“…1A). Values of Na ϩ i are generally lower, when determined with fluorescent probes, which measure free Na ϩ i , than with indirect methods that use, for example, isotopes or an electron probe to measure total Na ϩ i (16,17,19 Fig. 2A).…”
Section: Biological Effects Of Namentioning
confidence: 99%